THE CITY THAT BLESSED BIRUNI: HOW OLD IS IT? (TAMADDUN NURI JURNALI, 2025)
The article discusses the historical significance of the city of Kat (Fir, Pil, al-Fir) and its age. In this regard, the literature on history and linguistics on this issue is analyzed, and on this basis the author's observations are expressed and conclusions are drawn.